Pengaruh Literasi Ekonomi, Media Sosial, dan Kemudahan Transaksi terhadap Perilaku Ekonomi Rasional Generasi Z di DKI Jakarta - Nafilatul Ainiyeh; Suparno Suparno; Fitra Dila Lestari (Educational Journal, 2026)
This study aims to determine the influence of economic literacy, social media, and ease of transactions on rational economic behavior. Generation Z was selected because they tend to be responsive to trends and are therefore easily influenced to engage in consumptive behavior. The research design is quantitative, involving the distribution of questionnaires via Google Forms links both online and offline. This study was conducted in DKI Jakarta. The sampling technique used was purposive sampling. The respondents in this study were 210 members of Generation Z residing in DKI Jakarta. The data analysis technique used was descriptive analysis employing Structural Equation Modeling software based on Partial Least Squares, version 4.1.1.8. The results of this study indicate that economic literacy and social media significantly influence rational economic behavior. Meanwhile, transaction convenience does not influence rational economic behavior.